การวิเคราะห์อภิมานงานวิจัยปัจจัยเชิงผลของภาวะผู้นำการเปลี่ยนแปลงของพยาบาล - ศิริพร คล้ายทิม (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To 1)describe research charactiristics of consequence variables of transformational leadership of nurses; 2) identify the factors that influence consequence variables of transformational leadership of nurses; 3)compare means of correlation coefficients across consequence variables and research characteristics; 4) account variance of correlation coefficients by research characteristics varibles. The 26 Thai research studied during 1996-2004 were recruited. Study moderators including general, substantive, methodological charactiristics and research quality were collected. There were 145 correlation coefficients analyzed by using meta-analysis method of Glass, et al. Statistics used in this study were t-test, F-test and hierarchical stepwise regression analysis. The major findings were as follows 1) The research characteristics consisted of 3 components including general, substantive, methodological characteristics. 2) The consequence varibles were 5 factors: empowerment/motivation of staff nurses (r=.603), job satisfaction/organizational commitment (r=.436), job performance/effectiveness of leaders (r=.389), job performance of staff nurses (r=.290), and group/organization performance (r=.286), respectively. 3) Funding source, publication year, numbers of page excluding appendices, sample size, sample group, types of leadership theory, reliabilities of research instrument, and research quality were statistically and significantly affected on the mean of correlation coefficients of consequence variables of transformational leadership of nurses, at .05 level. 4) The predictors of correlation coefficients of consequence variables were reliabilities of research instrument, empowerment/motivation of staff nurses, job satisfaction/organizational commitment, job performance/effectiveness of leaders, sampling, research quality, funding source, duration of data collection, both correlated and predicted research and identifying significant level. They were accounted for 79.9 % of variance.